2020
DOI: 10.1186/s12986-020-00440-4
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin, a small molecular deriving from connectivity map (CMAP) screening, ameliorates obesity-induced metabolic dysfunction by enhancing brown adipose thermogenesis and white adipose browning

Abstract: Background: Obesity occurs when the body's energy intake is constantly greater than its energy consumption and the pharmacological enhancing the activity of brown adipose tissue (BAT) and (or) browning of white adipose tissue (WAT) has been considered promising strategies to treat obesity.Methods: In this study, we took a multi-pronged approach to screen UCP1 activators, including in silico predictions, in vitro assays, as well as in vivo experiments. Results: Base on Connectivity MAP (CMAP) screening, we obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 95 publications
2
10
0
Order By: Relevance
“…1 a). This is most probably due to reduction in adipose tissue mass caused by Indirubin treatment, as reported previously in mice 24 . The percentage of fibrosis also showed significant decrease in skeletal muscle of diabetic rats treated with IHZ.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…1 a). This is most probably due to reduction in adipose tissue mass caused by Indirubin treatment, as reported previously in mice 24 . The percentage of fibrosis also showed significant decrease in skeletal muscle of diabetic rats treated with IHZ.…”
Section: Discussionsupporting
confidence: 76%
“…Group IV (IHZ) rats received IHZ only at the above mentioned dose. IHZ dose was chosen based on the literature and our previous study 15 , 24 .…”
Section: Methodsmentioning
confidence: 99%
“…1a). This is possibly due to reduction in adipose tissue mass caused by Indirubin treatment as previously reported in mice [24]. The percentage of brosis also showed signi cant decrease in skeletal muscle of diabetic rats treated with IHZ.…”
Section: Discussionsupporting
confidence: 73%
“…However, the mechanism underlying regulation of rVFA expression during tumour progression in cells remains unclear. Notably, some studies have suggested that up-regulation of peroxisome proliferator-activated receptor gamma coactivator-1α (PGC1α) and uncoupled protein 1 (UCP1) expression in adipose tissues leads to a robust resistance to obesity and related diseases [ 39 , 40 ]. Functionally, the adipose tissue secretes various adipokines and cytokines, which can systemically regulate physiological functions through endocrine-like activity.…”
Section: Discussionmentioning
confidence: 99%